2002
DOI: 10.4269/ajtmh.2002.67.114
|View full text |Cite
|
Sign up to set email alerts
|

Natural host relationships and genetic diversity of Whitewater Arroyo virus in southern Texas.

Abstract: Abstract. The purpose of this study was to refine our knowledge of the natural host relationships of Whitewater Arroyo (WWA) virus. Two hundred eight rodents, representing nine species, were captured in July 1999 on the Chaparral Wildlife Management Area in southern Texas and tested for evidence of arenavirus infection. Antibody to an arenavirus was found in seven (21.9%) of 32 southern plains woodrats (Neotoma micropus) and none of 168 other rodents. Infectious WWA virus was isolated from four antibody-positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 12 publications
1
27
0
Order By: Relevance
“…are natural hosts of Tacaribe serocomplex viruses. Further, this study extends the known geographical distribution of Tacaribe serocomplex viruses in Texas from Dimmitt and La Salle counties (Fulhorst et al 2002b) to 10 other counties and provides the first evidence that Tacaribe serocomplex viruses are enzootic in Mexico.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…are natural hosts of Tacaribe serocomplex viruses. Further, this study extends the known geographical distribution of Tacaribe serocomplex viruses in Texas from Dimmitt and La Salle counties (Fulhorst et al 2002b) to 10 other counties and provides the first evidence that Tacaribe serocomplex viruses are enzootic in Mexico.…”
Section: Discussionsupporting
confidence: 55%
“…For example, the hispid cotton rat (Sigmodon hispidus) in southern Florida is the principal host of TAMV (Calisher et al 1970, Jennings et al 1970, and the southern plains woodrat (Neotoma micropus) in Dimmitt and La Salle counties in southern Texas is the principal host of CTNV (Fulhorst et al 2002b, Cajimat et al 2007a). Other natural hosts of Tacaribe serocomplex viruses in North America include the white-throated woodrat (N. albigula) in Arizona, Colorado, New Mexico, and Oklahoma, bushy-tailed woodrat (N. cinerea) in Utah, Mexican woodrat (N. mexicana) in Arizona, Colorado, New Mexico, and Utah, southern plains woodrat in Colorado, Stephen's woodrat (N. stephensi) in Arizona and New Mexico, Bryant's woodrat (N. bryanti, formerly N. lepida; Patton et al 2008), dusky-footed woodrat (N. fuscipes), large-eared woodrat (N. macrotis), brush mouse (Peromyscus boylii), California mouse (P. californicus), cactus deermouse (P. eremicus), North American deermouse (P. maniculatus), and western harvest mouse (Reithrodontomys megalotis) in California, and marsh oryzomys (Oryzomys palustris) in Florida , 2001a, 2002a, Kosoy et al 1996, Bennett et al 2000, Calisher et al 2001, Abbott et al 2004, Cajimat et al 2007b.…”
mentioning
confidence: 99%
“…In a previous study (Fulhorst et al 2002a), strains of CTNV were isolated from 5 southern plains woodrats, antiarenavirus was found in 4 (14.3%) of 28 other southern plains woodrats, and neither arenavirus nor anti-arenavirus antibody was found in 60 hispid cotton rats, 13 white-footed mice, 3 northern grasshopper mice, 1 northern pygmy mouse, 1 fulvous harvest mouse, 3 Ord's kangaroo rats, 62 Merriam's pocket mice, or 32 hispid pocket mice captured on the CWMA in a 1-week period in July 1999. Collectively, these findings suggested that the southern plains woodrat is the principal host of CTNV on the CWMA and that CTNV infection is highly specific to N. micropus.…”
Section: Discussionmentioning
confidence: 99%
“…The results of a previous study (Fulhorst et al 2002a) suggested that the southern plains woodrat (Neotoma micropus) in southern Texas is the principal host of CTNV. The objective of this study was to extend our knowledge of the ecology of CTNV.…”
mentioning
confidence: 93%
See 1 more Smart Citation